Encyclia × nizanburyi (Orchidaceae) un nuevo híbrido natural del Istmo de Tehuantepec, México - Pérez-García, Eduardo (2012)
Encyclia × nizanburyi, a new nothospecies only known from the region of Nizanda, on the Pacific watershed of the Tehuantepec isthmus, state Oaxaca, Mexico, is described and illustrated. The possible hybrid origin of the new taxon is discussed, and it is compared with its putative parents: Encyclia nizandensis and Encyclia hanburyi.